Association Between Parental Education, Occupation, Income, Language Activity, and Language Proficiency in Children - Aji Pratomo, Hafidz Triantoro; Adriani, Rita Benya; Akhyar, Muhammad (Indonesian Journal of Medicine, 2016)
Background: Language proficiency should be mastered by children before school admision. The process of language development was affected by cognitive and neurologic maturity. Language proficiency determine communication foundation, social and academic interaction. Children with retardation in language proficiency may encounter problem in the social and academic relationship. This study investigated the association between parental education, occupation, income, language activity, and language proficiency in children.Subjects and Method: This was an analytic observational study with cross sectional design. This study was conducted ÃÂ in Gondangrejo sub-district, Karanganyar, Central Java. A total sample of 102 children aged 4 to 5 years were selected for this study. The dependent variable was language proficiency. The independent variables were parental education, occupation, income, and language activity. The data were collected by a set of questionnaire and analyzed by multiple logistic regression.Results: Parental education Ã¢â°Â¥ senior high school (OR= 2.95; 95% CI= 1.03 to 8.39; p= 0.043), employed parents (OR= 3.45; 95% CI= 1.27 to 9.39; p= 0.015), family income Ã¢â°Â¥ regional minimum wage (OR= 6.35; 95% CI= 2.02 to 19.93; p= 0.002), and intense language activity (OR= 4.32; 95% CI= 1.61 to 11.51; p= 0.003) were associated with better language proficiency.Conclusion: Parental education Ã¢â°Â¥ senior high school, employed parents, family income Ã¢â°Â¥ regional minimum wage, and intense language activity are associated with better language proficiency.Keywords: parental education, occupation, language activity, language proficiency, childrenCorrespondence:ÃÂ Hafidz Triantoro Aji Pratomo. School of Health Polytechnics, Poltekkes Surakarta. Email: hafidzpoltekkes@gmail.comIndonesian Journal of Medicine (2016), 1(3): 152-159https://doi.org/10.26911/theijmed.2016.01.03.02